Open data & Big data ; Nouveaux défis pour la vie privée - Lyne Nantel (Communiquer)
The present review focuses on the book Open data & Big data; Nouveaux défis pour la vie privée, co-edited by D. Bourcier et P. De Filippi. This collaborative book, bringing together experts from disciplines like law, sociology, politics and ethics, aims to draw the new challenges of digital and massification of data on privacy.